2022
DOI: 10.1186/s12889-022-13490-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two multi-component behavior change interventions on cognitive functions

Abstract: Background We previously reported the effects of two cluster-randomized 6-month multi-component workplace interventions, targeting reducing sedentary behavior or increasing physical activity among office workers, on movement behaviors and cardiorespiratory fitness. The primary aim of this study was to investigate the effects of these interventions on cognitive functions compared to a wait-list control group. The secondary aims were to examine if changes in cognition were related to change in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…However, previous analyses based on the same RCT showed that participants already had high levels of accelerometer-measured PA (approximately 1.5 h of MVPA per day) but also high levels of SED (approximately 13 h) at baseline, despite efforts to enroll less active office workers [ 34 ]. The interventions had no average effects on accelerometer-measured MVPA, SED [ 35 ], 24-h movement behavior [ 34 ], movement behavior during work or non-work time [ 34 ], cardiorespiratory fitness [ 34 ] or cognitive functions [ 36 ]. However, the interventions increased autonomous and controlled motivation among iPA participants [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous analyses based on the same RCT showed that participants already had high levels of accelerometer-measured PA (approximately 1.5 h of MVPA per day) but also high levels of SED (approximately 13 h) at baseline, despite efforts to enroll less active office workers [ 34 ]. The interventions had no average effects on accelerometer-measured MVPA, SED [ 35 ], 24-h movement behavior [ 34 ], movement behavior during work or non-work time [ 34 ], cardiorespiratory fitness [ 34 ] or cognitive functions [ 36 ]. However, the interventions increased autonomous and controlled motivation among iPA participants [ 37 ].…”
Section: Introductionmentioning
confidence: 99%